Medicinal plants new vistas of research - Govil, J.N.; Govil, J.N.; Singh, V. K.; Hashmi, Shamima (New Delhi Today & Tomorrow's Printers and Publishers, 1993)
Contributed articles
Includes bibliographical references and index.
Keywords: Materia medica, Vegetable -- Research -- India; Medicinal plants -- Research -- India